Does an in-season detraining period affect the shoulder rotator cuff strength and balance of young swimmers? - Batalha, N. M.; Raimundo, A. M.; Tomas-Carus, P.; Marques, M. A. C.; Silva, A. J. (The Journal of Strength and Conditioning Research, 2014)
Imbalance in shoulder rotator muscles is a well-documented problem in swimmers, and it is important to implement land-based strength training programs. Meanwhile, the effects of a detraining period on swimmers' shoulder rotator muscles are unknown. The purpose of this study was to analyze the effects of a strength training program and detraining on the strength and balance of shoulder rotator cuff muscles in young swimmers, despite the continuity of usual water training. An experimental group (n = 20) and a control group (n = 20) of young male swimmers with the same characteristics (age, body mass, height, training volume, and maturational state) were evaluated. In both groups, the peak torques of shoulder internal (IR) and external (ER) rotators were assessed during preseason, midseason (16 weeks), and postseason (32 weeks). The experimental group underwent a strength training regimen from baseline to 16 weeks and a detraining period from 16 to 32 weeks. Concentric action at 60°/s and 180°/s was measured using an isokinetic dynamometer. The ER/IR strength ratios were obtained. At 60°/s, there were significant increments in IR strength and the ER/IR ratio in both shoulders. This trend was the same throughout the competitive season. The tendency was the same at 180°/s because training effects were noted primarily in IR and ER/IR ratios. Moreover, the absence of land-based strength training, from 16 to 32 weeks, revealed a reduction in the ER/IR ratio values in both shoulders. Our findings suggest that young swimmers' coaches should use dry-land strength training protocols, and that it is recommended that these should be conducted on a regular basis (during the whole season).